(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2015)
This work presents an experimental study of elastic-plastic behaviour of steel-concrete composite sections. The specimens are made of steel I-beam section completely embedded in parallelepiped concrete block. After testing, some specimens have shown apparent ductile behaviour before failure. This is mainly due to the plasticization of the tensile zone steel sections. Others did not have such ductility because of excessive cracking of the concrete in the compressive zone. It is necessary to clearly identify the existence of a plasticity zone after flowing and before rupture, to better understand the behaviour of this type of structures.